Theoretical Analysis of Multimetal Complexation of Pr(III):L-leucine:Mg(II): Thermo-Kinetic Studies of the Reaction Pathways - Thakro, Zevivonü; Ziekhrü, Mhasiriekho; Chizo, Shepazo; Devi, M. Indira (Asian Journal of Chemistry, 2026)
The 4f-4f absorption spectra of Pr3+ were employed as sensitive probes to investigate the interaction of Pr3+ with L-leucine in the presence and absence of Mg2+ in various aquated organic solvents, namely DMF, acetonitrile (ACN), dioxane and methanol. The interaction of Pr3+ with L-leucine was evaluated through the determination of spectroscopic energy parameters, including the Slater-Condon parameters (Fk), spin-orbit coupling parameter (ξ4f), bonding parameter (b1/2), nephelauxetic ratio (β), percentage covalency (δ) and Racah parameter (Eᵏ). These parameters were used to assess changes in the electronic environment and the nature of metal–ligand interactions. Variations in the absorption intensity parameters, including the oscillator strengths (P) of the individual 4f-4f transitions and Judd-Ofelt intensity parameters (Tλ), provided further evidence for the coordination of L-leucine with Pr3+. Upon addition of L-leucine, the characteristic absorption bands of Pr3+ exhibited bathochromic shifts accompanied by hyperchromic effects, which confirmed the changes in the coordination environment and electronic structure of the metal ion. The influence of Mg2+ on the Pr3+–L-leucine interaction was further examined to elucidate its role in the complexation process. Kinetic and thermodynamic investigations were subsequently performed to determine the mechanism, stability and energetics of complex formation in the different solvent systems. The combined spectroscopic, kinetic and thermodynamic results provide insight into the nature of Pr3+–L-leucine interactions and the influence of Mg2+ and solvent environment on their complexation behaviour.